Opening the envelope of health care information systems research. Issue 3 (September 2018) - Davidson, Elizabeth; Baird, Aaron; Prince, Karl
Abstract: In 2004, Chiasson and Davidson published a challenge to the scholarly Information Systems (IS) field to embrace health information systems research more fully within its mainstream research interests. In the ensuing 14 years, health care research has become an acknowledged specialization within the IS field. In this review article, we examine how health care research publications have developed within the IS field's leading journals since 2004 and explore the analytical and technological areas of focus within these publications. In addition to providing a descriptive overview of such research, we also examine three topical clusters in-depth (health IT adoption and diffusion, physician resistance to health IT use, and health IT impact on health care or system outcomes) to consider how researchers have addressed the challenge of developing general IS knowledge within this distinctive research context while also contributing contextually-relevant insights to the health care field. Finally, we discuss the implications of these analyses and suggest potential areas for future research. Overall, we contribute a foundation for IS health care researchers to consider how to position their work to contribute to knowledge through informational and organizational theory as well as to address important concerns of practice at the intersection of health and IS. Highlights: Evaluates HIT research published in Information & Organization and other leading IS journals from 2004 to 2017 Identifies analytical and technological areas of focus for considered HIT research Analyzes selected thematic clusters of considered HIT research Considers emerging areas of HIT focus in the information systems field with regards to health industry trends